(untitled) (International Journal of Language, Literacy and Translation, 2024)
Prosper Mérimée’s novella Carmen is a significant literary achievement, capturing the fascination of numerous literary enthusiasts and scholars. Its allure stems from its intricate narrative structure, rich historical and cultural elements, and a compelling love story. Genette summarized a set of theoretical systems applicable not only to this work but also to other works and this theory was later used by many researchers to analyze literary works, which includes narrative time, narrative mood, and narrative voice. This paper employs Genette’s narrative theory to examine the narrative features in this novel, specifically focusing on the application of narrative level and narrator in the novel, for these two aspects are the most outstanding and essential characteristics of this novel. Through a comprehensive analysis of the distinct narrative levels and the nuanced role of the narrator in Carmen, the paper draws clear conclusions. Mérimée deliberately constructs two narrative levels and employs dual narrators to unveil a narrative that is both intricate and transparent in its development. In Carmen, Mérimée utilizes the first and second narrative levels to unfold a poignant love tragedy featuring protagonists with contrasting qualities. Additionally, Mérimée employs two narrators, the amateur historian and Don Jose, to depict the female protagonist’s adventurous life and her unwavering pursuit of freedom. This study applies narrative theory to literary analysis, facilitating interpretation of the author’s narrative techniques and encouraging critical engagement with literature. Furthermore, this study is hoped to inspire more scholars and researchers to explore Carmen and Mérimée’s other works.